A Modern Approach to Risk Stratification in Patients with Heart Failure with Preserved and Reduced Ejection Fraction - Samadova Nigina Alisherovna; Madjidova Gulbahor Tolibovna; Yaxyoev Azim Akmalovich; Melikov Ulug'bek Shavkatovich (Genius Publishing Group, 2022)
A comparative analysis of left ventricular systolic dysfunction and heart failure with preserved left ventricular ejection fraction was carried out. 69 patients with heart failure FC III–IV according to NYHA were examined. In the group of chronic heart failure with preserved ejection fraction (40% of patients), women predominate, older people with a significantly higher body mass index, suffering from diabetes mellitus, anemia. In these patients, creatinine and cholesterol levels are significantly higher, and hemoglobin levels are significantly lower than in patients with left ventricular systolic dysfunction
Keywords: chronic heart failure; preserved left ventricular ejection fraction; left ventricular systolic dysfunction